THE CAVE ART OF YAMOR, UPPER FORTALEZA RIVER BASIN, BOLOGNESI - ANCASH - van Dalen Luna, Pieter (2015)
This article presents the characteristics of the sites associated with pictographs or quillqas funeral chullpas type structures that exist in the jurisdiction of the people and Rural Community Yamor in the district of Antonio Raymondi. These quillqas were drawn on the walls of large rocky cliffs, at different heights relative to the surface, painted with oxide of iron in large amounts around Yamor.